Chemical composition of the hydro-cryogenic system of lakes Munozero and Urozero (Republic of Karelia, Russia) - A. V. Sabylina; T. A. Efremova; O. I. Ikko (Лëд и снег, 2020)
The article presents the results of researches on the content of ions, biogenic and organic substances in the system «snow on ice – ice – under the ice water» in two lakes – Munozero and Urozero (Russia, Republic of Karelia), conducted in February 2019. Since the beginning of the 1990s, the southern and south-western parts of the catchment and the water area of Lake Munozero have been undergone the anthropogenic impact by discharges of domestic waste waters and feed from the trout farm. Influence of human activities upon the Lake Urozero is negligible. Composition of its under-ice water is bicarbonate-calcium. Among the inorganic forms of nitrogen-containing compounds in snow, ice and the under-ice water, the nitrate ion prevails (85%). High concentrations of total phosphorus (up to 10 μg/l) and organic nitrogen (up to 0.19 mg/l) in the lower layers of ice in the system “ice-water” for the Lake Munozero are comparable with the content of them in the under-ice water. The ice cover of both lakes Munozero and Urozero is characterized by a low content of organic carbon (on average, 1.0 and 0.8 mg/l), while in the under-ice water its concentration is 4 and 2 times higher, respectively. To determine the intensity of the involvement of dissolved substances into the ice in combination with ice-forming water, the coefficient of involvement Kv was used. Studies have shown that among the cations in the ice of both lakes, potassium is more involved, while among the anions this is the sulfate ion. In Lake Munozero, undergone the anthropogenic effects, the concentration of chlorine ions in the ice changes from 0.2 to 0.5 mg/l (17 and 36%‑eq).